2006
DOI: 10.1039/b514558a
|View full text |Cite
|
Sign up to set email alerts
|

Conformational arm-wrestling: battles for stereochemical control in benzamides bearing matched and mismatched chiral 2- and 6-substituents

Abstract: The orientation of a tertiary amide group adjacent to an aromatic ring may be governed by the stereochemistry of an adjacent chiral substituent. With a chiral substituent in both ortho positions, matched/mismatched pairs of isomers result. Evidence for matched stereochemistry is provided by the clean NMR spectra of single conformers, while mismatching gives poor or unexpected selectivities in the formation of chiral substituents, or mixtures of amide conformers. Attempts to use the match-mismatch effect to sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nucleophilic aromatic substitution is generally less sensitive to steric hindrance than the metal‐catalyzed coupling reactions commonly used to make diaryl ethers,9 and we found that the potassium salts of even rather hindered phenols 5 readily displaced the chloride group from 4 (made by lithiation of nitrile 3 10) to obtain ethers 6 a – 11 a in good yield. A sequence of addition, protection,11 oxidation, and reduction reactions yielded the further series of compounds 6 – 11 shown in Scheme . Directed ortho ‐metalation is a powerful way of building sterically congested aromatic substitution in a regiocontrolled manner,12 and the reported13 sequence of lithiation and oxidation reactions shown in Scheme gave further ethers 14 – 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Nucleophilic aromatic substitution is generally less sensitive to steric hindrance than the metal‐catalyzed coupling reactions commonly used to make diaryl ethers,9 and we found that the potassium salts of even rather hindered phenols 5 readily displaced the chloride group from 4 (made by lithiation of nitrile 3 10) to obtain ethers 6 a – 11 a in good yield. A sequence of addition, protection,11 oxidation, and reduction reactions yielded the further series of compounds 6 – 11 shown in Scheme . Directed ortho ‐metalation is a powerful way of building sterically congested aromatic substitution in a regiocontrolled manner,12 and the reported13 sequence of lithiation and oxidation reactions shown in Scheme gave further ethers 14 – 16 .…”
Section: Methodsmentioning
confidence: 99%
“…This spectroscopic feature has been noted previously, 47 and we now routinely make use of it to identify endo and exo oxazolidines. 48,49 The differing stereoselectivities of the two condensations of 26 are presumably the result of kinetic vs. thermodynamic control. Agami 47 showed that condensation of aldehydes with (−)ephedrine gives exo oxazolidines as the thermodynamic products but that reactions in polar solvents or with electron-deficient aldehydes yield initially endo oxazolidines, which only slowly epimerise to exo.…”
Section: (−)-Pseudoephedrine-and (−)-Ephedrine-derived Oxazolidinesmentioning
confidence: 99%
“…The synthesis of the naphthamides detailed in Table 1, along with benzamides 4a, 7 4b 31 17, 14 22, 14 and 23 14 have been published previously. Benzamide 14 is published in the following paper, 49 and diamide 25 67 will be published in the context of related research shortly. (3 × 25 ml), dried (MgSO 4 ) and evaporated under reduced pressure.…”
Section: Published Elsewherementioning
confidence: 99%